Ronald Reagan and the 1980s
XIII, 268 p.
Keywords: By the end of the 1980s, many Americans looked at the state of the nation with a renewed optimism, which was personified by an enduring American president - Ronald Wilson Reagan. The essays in this volume revisit the 1980s in order to examine the factors that contributed to his political and cultural triumphs and assess his legacy.